EspH interacts with the host active Bcr related (ABR) protein to suppress RhoGTPases - Rachana Pattani Ramachandran; Ipsita Nandi; Nir Haritan; Efrat Zlotkin-Rivkin; Yael Keren; Tsafi Danieli; Mario Lebendiker; Naomi Melamed-Book; William Breuer; Dana Reichmann; Benjamin Aroeti (Gut Microbes)
Enteropathogenic Escherichia coli are bacterial pathogens that colonize the gut and cause severe diarrhea in humans. Upon intimate attachment to the intestinal epithelium, these pathogens translocate via a type III secretion system virulent proteins, termed effectors, into the host cells. These effectors manipulate diverse host cell organelles and functions for the pathogen’s benefit. However, the precise mechanisms underlying their activities are not fully understood despite intensive research. EspH, a critical effector protein, has been previously reported to disrupt the host cell actin cytoskeleton by suppressing RhoGTPase guanine exchange factors. However, native host proteins targeted by EspH to mediate these activities remained unknown. Here, we identified the active Bcr related (ABR), a protein previously characterized to possess dual Rho guanine nucleotide exchange factor and GTPase activating protein (GAP) domains, as a native EspH interacting partner. These interactions are mediated by the effector protein’s C-terminal 38 amino acid segment. The effector primarily targets the GAP domain of ABR to suppress Rac1 and Cdc42, host cell cytotoxicity, bacterial invasion, and filopodium formation at infection sites. Knockdown of ABR expression abolished the ability of EspH to suppress Rac1, Cdc42. Our studies unravel a novel mechanism by which host RhoGTPases are hijacked by bacterial effectors.